SERUM CYSTATIN C LEVELS IN COPD: POTENTIAL DIAGNOSTIC VALUE AND RELATION BETWEEN RESPIRATORY FUNCTIONS - Telo, Selda; Kuluozturk, Mutlu; Deveci, Figen; Kirkil, Gamze; Oner, Onsel; Kaman, Dilara (De Gruyter Poland Sp Zoo, 2018)
Background: The aim of this study was to determine the level of serum cystatin C (CysC) in patients with Chronic Obstructive Pulmonary Disease (COPD) during exacerbation and stable periods and to investigate its potential diagnostic value and the relationship between CysC levels and the pulmonary function test (PFT). Methods: One hundred twenty-six patients with COPD (68 in stable periods, 58 during exacerbation periods) and 50 healthy subjects were included in the study. PFT, body mass index (BMI), white blood cell counts, C-reactive protein (CRP), serum urea and creatinine levels were evaluated in both groups of patients. CysC levels were measured in all participants. Results: Serum CysC levels were statistically higher in both COPD groups than the control group (p<0.001 for both) although there was no statistically significant difference between COPD groups (p>0.05). CysC levels showed negative correlation with forced expiratory volume in 1 second (FEV1) and a positive correlation with C-reactive protein (CRP) levels in patients with stable COPD. There was a positive correlation between serum CysC levels and serum urea, creatinine, CRP levels in patients with COPD exacerbation (r=0.333, p=0.011; r=0.260, p=0.049; r=0.414, p<0.01 respectively). When stable COPD and control groups were evaluated, serum CysC had an area under the curve (AUC) in the receiver operating characteristic (ROC) curve of 0.951 (0.909-0.994 95% CI: p<0.001). Conclusions: Our results showed that CysC levels increased in both COPD groups. Increased CysC levels may be related with lung function decline and inflammation in COPD patients. In addition, CysC levels may be a potential indicator for the diagnosis of COPD.
SERUMSKI NIVOI CISTATINA C U HRONI?NOJ OPSTRUKTIVNOJ BOLESTI PLU?A: POTENCIJALNA DIJAGNOSTI?KA VREDNOST I ODNOS IZME?U RESPIRATORNIH FUNKCIJA
Keywords: COPD; cystatin C; pulmonary function